Information sharing and cross-border entry in European banking - Caterina Giannetti; Nicola Jentzsch; Giancarlo Spagnolo (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Information asymmetries can severely limit cross-border border expansion of banks. When a bank enters a new market, it has incomplete information about potential new clients. Such asymmetries are reduced by credit registers, which distribute financial data on bank clients. We investigate the interaction of credit registers and bank entry modes (in form of branching and M&A) by using a new set of time series cross-section data for the EU-27 countries. We study how the presence of public and private credit registers and the type of information exchanged affect bank entry modes during the period 1990-2007. Our analysis shows that the existence of both types of registers increases the share of branching in the overall entries. Additionally, the establishment of public registers reduces concentration ratios, and some banking competition indicators (such as overhead costs/assets). The introduction of a private credit bureau, on the other hand, has no effect on concentration ratios, but positively contributes to competition (by decreasing interest rate margins). This suggests that credit registers facilitate direct entry through a reduction of information asymmetries, which in turn intensifies competition.
Keywords: F37; G21; G34; L13; O16; 330; Credit registries; foreign entry; asymmetric information; Internationale Bank; Internationale Markteintrittsstrategie; Informationsaustausch; Kreditwürdigkeit; Auskunftei; EU-Staaten